Essential facilitators in building university partnership with ethnic minority communities - Kim, Caleb (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales)

(untitled) (Département de communication sociale et publique, Université du Québec à Montréal, 2021)
Recently, universities have paid attention to partnership with local communities for mutual benefits. However, this partnership is a complex and challenging process because it brings two different organizations to work together. Many challenges encountered often produces dissatisfying results and distrust among all participants. Using the BRAVE youth violence prevention program as a case study, this study describes the essential facilitators affecting the university partnership with disadvantaged poor ethnic communities in Chicago. Identified facilitators are: agreed mutual benefits, trust relationship, open and transparent communication, shared missions and interest, equal power in decision-making, empowering organization’s sustainability, flexibility, and cultural activities. Building on the lessons from this case example, this study presents that the university-community partnership demonstrates a shared responsibility of the university to serve community members and of the partner agency’s commitment to strengthen the community’s capacity to prevent youth violence.